Classic Galactosemia: A Rare Cause of Neonatal Jaundice in Infants - Fahad Gul, Hashim Khan, Muhammad Tahir Konain, Syeda Mamoona Qudrat, Muhammad Ashraf (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Classic galactosemia is a rare inborn error of galactose metabolism which is caused by a deficiency of an enzyme known as galactose-1-phosphate uridyl transferase (GALT). A 4-month-old male infant presented with yellowish discolouration of the skin and eyes (jaundice) and clay-coloured stools. On examination, the baby has normal development and no signs of chronic liver disease. Blood tests and ultrasound show raised bilirubin and liver enzymes, but no structural abnormality or biliary atresia. However, urine sugar chromatography detected galactose and lactose, and a direct enzyme assay confirmed a deficiency of galactose-1-phosphate uridyl transferase. The patient was treated with a galactosemia-based diet, non-lactose milk, and vitamin supplements and showed improvement. The patient is currently on follow-up for monitoring Keywords: Classic galactosemia, neonatal jaundice, GALT deficiency, dietary modification, inborn errors of metabolism